2019
DOI: 10.1371/journal.pone.0219582
|View full text |Cite
|
Sign up to set email alerts
|

Correction: From North American hegemony to global competition for scientific leadership? Insights from the Nobel population

Abstract: The graph for S4 Fig is incorrect and the legends for S4-S6 Figs are incorrect. Please see the corrected S4-S6 Figs below. Supporting information S4 Fig. Master-apprentice relations in Chemistry (North America). Master-apprentice relations among Nobel laureates in Chemistry (North America). Underlined names are from other regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Based on the entire population of Nobel laureates in science from 1901 to 2017, Heinze et al (2019) found, in a study that, North America's rise as global power in science started in the 1920s and consolidated in 1970s but in 2000, its scientific hegemony witnessed a downward trend as its share of laureates across disciplines dropped. The research in its further findings explained that:…”
Section: Recent Studies On the Us Hegemonic Power And China As Hegemony Pretendermentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the entire population of Nobel laureates in science from 1901 to 2017, Heinze et al (2019) found, in a study that, North America's rise as global power in science started in the 1920s and consolidated in 1970s but in 2000, its scientific hegemony witnessed a downward trend as its share of laureates across disciplines dropped. The research in its further findings explained that:…”
Section: Recent Studies On the Us Hegemonic Power And China As Hegemony Pretendermentioning
confidence: 99%
“…North America has become apparently less effective since 2010 in transferring capacities for conducting ground-breaking research from one generation of scientists to another. Heinze et al (2019) North America's scientific hegemony has often been attributed to the organizational design of its research universities, which compete more actively for scientific talent and adopt scientific innovations faster than universities and research institutions in Europe (and elsewhere). In another view, it is observed that while the US is busy with excitement derived in waging wars with some developing countries as custodian of the position of world superpower, China is busy, strategically penetrating with its soft power capacity in Africa and Asia axis.…”
Section: Recent Studies On the Us Hegemonic Power And China As Hegemony Pretendermentioning
confidence: 99%
See 1 more Smart Citation